Development of Teaching Materials in the Form of Modules Using Creative Problem Solving (CPS) Learning Models on Quadrilateral and Triangle Materials for SMP/MTs Students - Hazmi M, Marina (Holistic Science, 2022)
This research aims to develop teaching materials in modules using creative problem solving (CPS) models in rectangular and triangular materials at the SMP / MTs level. CPS is a variation of problem-solving learning with systematic techniques in organizing creative ideas to solve a problem. An open-ended problem is an open problem presentation approach. The test subjects were taken using purposive sampling techniques in students of Class VII of Al-Washliyah Private Junior High School. The method used in this study was development research with a 4-D model from Thiagarajan (Define, Design, Develop, and Disseminate). According to expert assessments, the results of research show that the teaching materials developed have good criteria based on the quality of aspects of material coverage, language, presentation techniques, stages of creative problem solving (CPS) learning models based on open-ended problems, and learning assessments. Assessment according to student response based on the quality aspects of the suitability of material content, physical condition, and benefits of use has good criteria. Thus, this teaching material is included in the criteria and can be used in class VII math learning.